1999
DOI: 10.1007/bf02483054
|View full text |Cite
|
Sign up to set email alerts
|

A double bifurcated graft for abdominal aorta and bilateral iliac artery reconstruction

Abstract: Revascularization of the hypogastric artery often tends to be neglected in aortoiliac reconstructive surgery; however, its incomplete revascularization can result in unfavorable complications such as buttock claudication or necrosis, vascular impotence, and colonic ischemia. Multiple vascular lesions in the abdominal aorta and bilateral iliac arteries were reconstructed using a newly designed double bifurcated graft in five male patients. All five patients demonstrated excellent graft limb patency and postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…It is controversial whether a more extensive approach toward revascularization of the internal iliac arteries is needed to limit the risk of postsurgical proximal ischemia in aortobifemoral bypass. 12,14,15 This may be attributable to the difficulty in proving the vascular origin of the symptoms by using noninvasive methods. Recently, there has been a renewed interest in hip/buttock claudication caused by lesions in one or both of the internal iliac arteries because of the development of endovascular procedures that allow easier access to these vessels compared with surgical techniques.…”
mentioning
confidence: 99%
“…It is controversial whether a more extensive approach toward revascularization of the internal iliac arteries is needed to limit the risk of postsurgical proximal ischemia in aortobifemoral bypass. 12,14,15 This may be attributable to the difficulty in proving the vascular origin of the symptoms by using noninvasive methods. Recently, there has been a renewed interest in hip/buttock claudication caused by lesions in one or both of the internal iliac arteries because of the development of endovascular procedures that allow easier access to these vessels compared with surgical techniques.…”
mentioning
confidence: 99%
“…Representa de 2 a 7% dos aneurismas intra-abdominais 3,4 , ocorrendo principalmente na sétima década de vida 1,2 .…”
unclassified
“…Apesar de geralmente permanecerem assintomáti-cos 1,3,4 , tendo seu diagnóstico durante exames rotineiros de imagem 3 , quando sintomáticos, os aneurismas das artérias ilíacas podem levar à dor, compressão de órgãos vizinhos, ruptura para estruturas adjacentes 2 , trombose e embolização 4 . São relatados sintomas vagos de dor abdominal e no quadril, queixas geniturinárias e claudicação 1 .…”
unclassified
See 1 more Smart Citation
“…This graft was released in 2000 in Europe and March 2008 in Japan. The first clinical report was by Cruz et al [4], which reported on the use of a quadrifurcated prosthesis in one case of AAA with iliac arterial lesion, and Akiyama et al [5] reported on favorable results in five cases. Recently, the number of cases of open surgery for AAA with iliac arterial aneurysm or occlusive disease have been increasing, and InterGard TM Quadrifurcated is expected to have more opportunities to deal with these complex cases [1].…”
Section: Discussionmentioning
confidence: 99%